Development and Application of Downhole Chokes with Pressure and Temperature Monitoring Function. Issue 1 (1st January 2022) - Chen, Jiaxiao; Tan, Jinfeng; Yu, Fan; Chen, Ke; Jiang, Mi
Abstract: For wells employing downhole choking technology, the traditional well testing methods no longer accommodate the requirements for dynamic monitoring of production performance due to the existence of downhole chokes. On one hand, the wellhead pressure data of gas wells with downhole chokes can neither truly reflect the actual situation of gas wells nor directly provide effective data for the dynamic gas well performance analysis. On the other hand, because of the calculation error with the nozzle flow pressure drop in the calculation method, the calculation error of wellbore pressure is significant, resulting in failure of the annulus liquid level method to carry out monitoring as most wells are installed with packers. In this regard, the downhole choke with pressure and temperature monitoring function has been independently developed by combining the production features of the wells with downhole choking technology. Under the condition of no change of tubing string, no use of cable running and no impact on gas well production, the steel wire operation was implemented, achieving the downhole choking production of gas wells and the monitoring of pressure and temperature prior to the choking operation, thus to establish a wellbore pipe flow prediction model and a nozzle flow model. Through the field application and evaluation, the error between the calculation results of the flow model and the field measured data is controlled within 5%, which provides a theoretical calculation basis for the accurate pressure prediction of wells using choking technology as well as technical support for the dynamic analysis of downhole choking gas wells.